2012
DOI: 10.1364/ol.37.004561
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate 1 GHz repetition rate femtosecond optical parametric oscillator

Abstract: We report a degenerate femtosecond optical parametric oscillator (OPO) that is synchronously pumped by a mode-locked Ti:sapphire laser at 1 GHz repetition rate. The OPO produces an 85 nm (10 THz) wide frequency comb centered at 1.6 μm. Stable long-term operation with >100 mW of average output power has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Note that in the case of a degenerate doubly-resonant SP-OPO only the envelope spectrum of the MIR comb changes, not the comb line positions, which are tightly locked to the pump comb [10,13]. Passive thermal locking can often maintain SP-OPO oscillation for several minutes or more [7,14], albeit with poor stability of the output power and spectrum, unless a crystal of large thermal effect, such as GaAs, is used [15]. In practice, active locking of the resonator length is usually needed.…”
Section: Synchronously Pumped Optical Parametric Oscillator (Sp-opo) mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in the case of a degenerate doubly-resonant SP-OPO only the envelope spectrum of the MIR comb changes, not the comb line positions, which are tightly locked to the pump comb [10,13]. Passive thermal locking can often maintain SP-OPO oscillation for several minutes or more [7,14], albeit with poor stability of the output power and spectrum, unless a crystal of large thermal effect, such as GaAs, is used [15]. In practice, active locking of the resonator length is usually needed.…”
Section: Synchronously Pumped Optical Parametric Oscillator (Sp-opo) mentioning
confidence: 99%
“…3) [12]. Another problem of this method is that the top of an oscillation peak can be irregular [11,14] or flat, such as peak D in Fig. 2, prohibiting precise locking to the peak.…”
Section: Synchronously Pumped Optical Parametric Oscillator (Sp-opo) mentioning
confidence: 99%
See 1 more Smart Citation
“…It also has been shown that the frequency comb salient features, such as carrier envelope offset and repetition rate, are transferred to the mid-IR at degeneracy [8]. Thus, using a high repetition rate near-IR source, SPOPOs show promise for extending the mentioned applications into the mid-IR [9].…”
mentioning
confidence: 99%
“…The octave-spanning output spectrum in a wavelength range containing several molecular fingerprints (OH, CH, CO, and NH) suggests the potential of the OPO for precision frequency comb spectroscopy after CEP stabilization. Later, operation of a degenerate fs OPO based on a 1-mm MgO:PPLN crystal pumped by a 30-fs KLM TiS laser at 1 GHz was reported, generating $85-nm-wide spectrum centered at 1.6 m with 9 100-mW average power [11]. Stable phase-locked comb generation was evidenced by measurements of RF spectrum, confirming a single indistinguishable signal-idler output comb at exact degeneracy with a mode spacing of 1 GHz.…”
mentioning
confidence: 99%